The Implementation of JABBALAB Online Site as a Source of Independent Learning for German Students, State University of Malang - Moh Chandra Afandi (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
The purpose of this study is to describe how students use and respond to the online site JABBALAB as an independent learning resource. This research uses descriptive qualitative method. The Sources of data in this study were German students, Universitas Negeri Malang. Data collection techniques used are field notes, questionnaires, and interview. Based on the results of field notes and questionnaires, it was explained that as long as students did independent learning through the online site JABBALAB, researchers did not get complaints or questions from students. This shows that students have no difficulty when using the site. And based on the results of the interview, students thought that the site was interesting and easy to understand because it was equipped with animated videos and also quizzes. Therefore, students will continue to use the JABBALAB online site as a source of independent learning at home. Even so, there are obstacles experienced by students when using the site, namely requiring a strong internet network and requiring extra internet quota to be able to access the site smoothly.